(untitled) (Social Science Review, 2022)
The burgeoning rise of preventable reasons of maternal deaths is highlighted as a prime concern for maternal health in Bangladesh. The main objective of this study was to assess the preparedness of health facilities to provide institutional delivery in Bangladesh. This study utilized data from the 2017 Bangladesh Health Facility Survey. Readiness of 1600 health facilities were measured using the service availability and readiness assessment manual of the World Health Organization. Health facilities were classified into public, private facilities, and NGO. Among the 1600 health facilities measured in this study, public facilities showed higher availability of normal delivery readiness whereas private facilities showed higher availability of caesarean delivery readiness. This study found a significant geographical variation in terms of readiness of health facilities to provide institutional delivery. In order to minimize the burden of preventable maternal deaths in Bangladesh, urgent improvement in all levels of health facilities, especially in health facilities of rural areas it is prerequisite to achieve the maternal health related targets of SDGs. Social Science Review, Vol. 38(1), June 2021 Page 17-32